IMPLEMENTASI METODE PEMBELAJARAN COOPERATIVE LEARNING TEKNIK THINK PAIR SHARE UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA ISLAMIYAH ASSYAFI'IYAH TAMBERU AGUNG BATU MARMAR PAMEKASAN - Nopiyatul Fittri; Moh. Afiful Hair (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Cooperative Learning method with the Think Pair Share (TPS) technique in increasing student learning activity at Assyafi'iyah Tamberu Agung Batu Marmar Pamekasan Islamic Junior High School and to identify factors that support the effectiveness of its implementation. The research is motivated by the low participation of students during the learning process which is indicated by the lack of courage to ask questions, express opinions, and participate in class discussions as described in the research proposal. The study uses a qualitative approach with a phenomenological research type. Data were obtained through observation, in-depth interviews, and documentation of the principal, Islamic Religious Education teachers, and students as the main data sources. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldana which includes data condensation, data presentation, and drawing conclusions, while the validity of the data was tested through triangulation of sources, techniques, and time. The results of the study indicate that the implementation of the Think Pair Share technique is able to create more participatory learning through the stages of independent thinking (think), discussing in pairs (pair), and sharing the results of the discussion in front of the class (share). These stages provide equal opportunities for each student to develop the courage to express opinions, improve communication skills, and build cooperation between students. Increased activeness is evident from the increasing intensity of asking questions, answering questions, presenting arguments, and student involvement during the learning process. However, the effectiveness of implementing this method is influenced by the teacher's readiness in managing the class, student characteristics, and learning time management. This study concludes that the Cooperative Learning method, using the Think Pair Share technique, is a relevant learning strategy for increasing student learning activeness in Islamic Religious Education subjects because it is able to transform learning from teacher-centered to student-centered learning.